ANALISIS RISIKO KESELAMATAN DAN KESEHATAN KERJA DI PT VAN OORD BATAM - Naibaho, Leonardo; Arista, Anggia (Computer Science and Industrial Engineering, 2023)
PT Van Oord Batam is an international company in of Batam. Based on the data from 2020-2022 there have been several cases of work accidents, to reduce accidents at workpace, it is necessary to conduct a program of prevention accidents. Risk assessment includes hazard identification, potential hazard analysis, risk assessment, risk control, monitoring and evaluation. In the process of identification and conducting analysis of potential hazards can use the Hazard and Operability study method. The Result is: there are 15 levels of risk of rotation of grind, splashes of steel dust of the ship wall, material emitted, noise emitted by the compressor, the splash of the wall paint of the vessel, the noise removed by chipping machine, a noise released by the grind, a fire splash when using a grind, exposed to welding light, the heat removed of the welding machine, brushes removed, brush noise, paint and tinner chemicals, dust removals from the wind of the Compressor, smoke removed during welding. The solution in the control or prevention of work accidents in the maintenance department of PT VAN OORD BATAM is the improvement of discipline in the use of PPE as well as adding to the K3 training program.